2009
DOI: 10.1179/136217108x370281
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady interfacial phenomena during inward weld pool flow with an active surface oxide

Abstract: Particle image velocimetry (PIV) was applied to estimate the velocity field on a weld pool surface with an oxide layer. A positive surface tension gradient drives an inward flow pattern from the boundary to centre of the weld pool, resulting in particles collecting on the centre line of the pool at the surface. Unsteady flow motions were observed by experimental visualisation of the particle flow, and the computed velocity field shows strong unsteady interfacial movement during inward flow. These unsteady flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…Previous numerical studies on heat and fluid flow in low-Prandtl melting pools with surfactants have shown that the molten metal flow can be very unstable at high Marangoni numbers [6,7,15]. However, deformations of the melt pool surface as observed experimentally [5,17] were not accounted for in those studies. The aim of the present work is to understand the effect of surface deformations on flow instabilities in a liquid metal melting pool with surfactant.…”
Section: Introductionmentioning
confidence: 97%
“…Previous numerical studies on heat and fluid flow in low-Prandtl melting pools with surfactants have shown that the molten metal flow can be very unstable at high Marangoni numbers [6,7,15]. However, deformations of the melt pool surface as observed experimentally [5,17] were not accounted for in those studies. The aim of the present work is to understand the effect of surface deformations on flow instabilities in a liquid metal melting pool with surfactant.…”
Section: Introductionmentioning
confidence: 97%
“…Although many results have been reported for oxygen effect in low-energy-density welding process, few have touched that in high-energy-density laser welding [38][39][40], especially in the keyhole mode welding. As the most commonly encountered welding atmosphere, air and argon are used as welding atmosphere and compared in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the temperature coefficient of surface tension is a function of temperature and surfactants content. The weld pool flow can be affected by the distributions of both the activating element and temperature at the weld pool [39,43]. This is an issue of significance to be given more focus sequentially.…”
Section: Grmentioning
confidence: 99%